2019
DOI: 10.1016/j.tsf.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al/Si atomic ratio on optical and electrical properties of magnetron sputtered Al1-xSixOy coatings

Abstract: This work presents a study on the influence of the Al/Si atomic ratio in dc magnetron sputtered Al 1-x Si x O y amorphous and transparent films upon their chemical composition, films' structure, optical and electrical properties. Increasing silicon in Al 1-x Si x O y films, from 0 at. % up to 31.1 at. %, caused an increment of deposition rate and an increment in Al-O-Si energy bonds as confirmed by XPS analysis. On other hand, the optical constants (refractive index (n) and extinction coefficient (k)), dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Moreover, Fourier transform infrared (FT-IR) spectra revealed that the Si–OH characterized peaks at 952 cm –1 became weaker with increasing proportions of the AlO X layer on the SiO 2 surface (Figure b) . In addition, in the high-resolution XPS spectra of Si 2p in Figure S4a, signals were associated with the Si–O–Si bond at the binding energy of 103.57 eV (QDs@SiO 2 ) and the Si–O–Al bond at 102.02 eV. , In the case of increasing AlO X proportion, the Si–O–Si bond decreased and the Si–O–Al bond became dominant in QDs@SiO 2 @AlO X -(2:1) and QDs@SiO 2 @AlO X -(1:1), respectively. Meanwhile, in the high-resolution XPS spectra of Al 2p in Figure S4b, the binding energies of Al–O–Al and Al–O–Si bonds were 73.91 and 74.74/75.01 eV for QDs@AlO X and QDs@SiO 2 @AlO X -(2:1)/QDs@SiO 2 @AlO X -(1:1), respectively. Therefore, these results indicated that the Si–O–Al bonds facilitated the AlO X layer growing on the SiO 2 surface with Si–OH bonds.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Fourier transform infrared (FT-IR) spectra revealed that the Si–OH characterized peaks at 952 cm –1 became weaker with increasing proportions of the AlO X layer on the SiO 2 surface (Figure b) . In addition, in the high-resolution XPS spectra of Si 2p in Figure S4a, signals were associated with the Si–O–Si bond at the binding energy of 103.57 eV (QDs@SiO 2 ) and the Si–O–Al bond at 102.02 eV. , In the case of increasing AlO X proportion, the Si–O–Si bond decreased and the Si–O–Al bond became dominant in QDs@SiO 2 @AlO X -(2:1) and QDs@SiO 2 @AlO X -(1:1), respectively. Meanwhile, in the high-resolution XPS spectra of Al 2p in Figure S4b, the binding energies of Al–O–Al and Al–O–Si bonds were 73.91 and 74.74/75.01 eV for QDs@AlO X and QDs@SiO 2 @AlO X -(2:1)/QDs@SiO 2 @AlO X -(1:1), respectively. Therefore, these results indicated that the Si–O–Al bonds facilitated the AlO X layer growing on the SiO 2 surface with Si–OH bonds.…”
Section: Resultsmentioning
confidence: 96%
“…40 In addition, in the high-resolution XPS spectra of Si 2p in Figure S4a, signals were associated with the Si−O−Si bond at the binding energy of 103.57 eV (QDs@SiO 2 ) and the Si−O−Al bond at 102.02 eV. 41,42 In the case of increasing AlO X proportion, the Si−O− Si bond decreased and the Si−O−Al bond became dominant in QDs@SiO 2 @AlO X -(2:1) and QDs@SiO 2 @AlO X -(1:1), respectively. Meanwhile, in the high-resolution XPS spectra of Al 2p in Figure S4b, the binding energies of Al−O−Al and Al−O−Si bonds were 73.91 and 74.74/75.01 eV for QDs@ AlO X and QDs@SiO 2 @AlO X -(2:1)/QDs@SiO 2 @AlO X -(1:1), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This creates an internal electric field that reduces the overall field within the dielectric itself. If a dielectric is composed of weak bond molecules, in this case, these molecules not only become polarized, but also reorient so that their symmetry axes align to the field (Amjad et al, 2019;Costa et al, 2019;Das and Choudhary, 2019;Liu et al, 2019;Sharma et al, 2019;Xie et al, 2019;Xu et al, 2019). Research conducted on the insulator revealed that low electrical conduction and dielectric materials with a high polarizability posse the latter which is expressed by a number called the relative permittivity.…”
Section: Introductionmentioning
confidence: 99%
“…2c the Si 2p core-level, where the two specimens have the common three peaks located at 100.6, 101.7 and 102.6 eV, which they recognized as Si(Al)-Si2N2, Si3N4 and Si-O-Al, respectively (Oliveira et al, 2015) (Costa et al, 2018)(Rebouta et al, 2015) (AL-Rjoub et al, 2017). The fourth peak of nitride sample (AlSiTiNP= 0.038 Pa) centered at 98.7 is considered as Si elemental bond (Z. L. Wu et al, 2015)(Oliveira et al, 2015).Finally, Al 2p core level is shown in Fig.2d, the two samples share the components centred at 73.9 and 74.8 eV related to Ti(Al)-N and Al-O, respectively(Z. L. (Wainstein and Kovalev, 2018) (Costa et al, 2018) (Rahman et al, 2016).…”
mentioning
confidence: 99%